Kingdom of Lesotho : Joint Staff Advisory Note on the National Strategic Development Plan. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2012)
Lesotho's National Strategic Development Plan (NSDP) serves as an implementation strategy for the national vision. It recognizes the significant challenges Lesotho faces in reducing poverty and making growth more broad-based. Overall, it presents a coherent analysis and offers an appropriate path forward to sustained poverty reduction and sustainable economic growth. Executive Directors find that a well-designed implementation and monitoring framework is necessary. Implementation of the NSDP will be a key challenge.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet